Service value chain: profit value chain - Ismail, Mohd.Fais; Mohd Nor, Nurul Nadiah; Selamat, Nuramalina; Amir Husain, Sofiah; Hamsaruddin, Siti Noorfairuz; Mansor, Noor Farazeha; A. Aziz, Nurul Asyirah; Hazmah Yasib, Sheery; T.K. Muthu Koya Thangali, Thahira Bibi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study explored the integration of service value chain principles into the profit value chain, emphasized how strategic improvisation led to innovative solutions and increased financial outcomes. Through a systematic approach, organizations can leverage resources, optimized service offerings, and responded dynamically to market competitiveness. This report aimed to provide practical guidance for stakeholders to enhanced the operational effectiveness and drive profitability